Trophic ecology of fish community at Nimbai Stream: Competition and predation interaction to Arfak rainbowfish, Melanotaenia arfakensis Allen, 1990 - Emmanuel Manangkalangi; M. Fadjar Rahardjo; Renny K Hadiaty; Sigid Hariyadi; Charles P. H. Simanjuntak (Jurnal Iktiologi Indonesia, 2019)
Information on trophic ecology can provide an understanding of the functional role of fish in an ecosystem, including endemic and native fish groups, as well as alien fish that are introduced through anthropogenic activities. The research on the trophic ecology of the fish community in the Nimbai Stream, Prafi River system, is intended to describe the interaction of competition and predation, especially towards endemic fish, Melanotaenia arfakensis. Fish samples were collected monthly from four habitat types, i.e., slow littoral, medium littoral, pool, and run from May 2016 to April 2017. A combination of an electric shocker and a hand net was used to collect fish samples. A total of 16 fish species were collected, consists of one endemic species, namely M. arfakensis, nine species of native fish, and six species of alien fish. The Arfak rainbowfish and three native fish species were categorized as insectivorous, four native fish species as herbivorous, and two other fishes as carnivorous. Three alien fish species also belong to insectivorous, two alien fish species as carnivorous, and one species as herbivorous. The niche breadth of fish communities ranges from 0.071 to 0.857. The trophic niche overlap between the Arfak rainbowfish and three native fish species and three alien fish species was recorded. The results of this study indicate a potential competition and predation interactions between Arfak rainbowfish and native fish as well as with alien fish species. Therefore, introducing alien fish into Prafi River system will disrupt Arfak rainbowfish population. Abstrak Informasi mengenai ekologi trofik dapat memberikan pemahaman tentang peran fungsional ikan dalam suatu ekosis-tem, termasuk pada kelompok ikan endemik, ikan asli, maupun ikan asing yang dimasukkan melalui aktivitas antro-pogenik. Penelitian mengenai ekologi trofik komunitas ikan di Sungai Nimbai, sistem Sungai Prafi, bertujuan untuk mendeskripsikan interaksi kompetisi dan pemangsaan, khususnya terhadap ikan endemik, Melanotaenia arfakensis. Contoh ikan dikumpulkan setiap bulan dari Mei 2016-April 2017 di empat tipe habitat yakni tepi aliran lambat, tepi aliran sedang, lubuk, dan aliran deras. Kombinasi alat electric shocker dan hand net digunakan untuk mengumpulkan contoh ikan. Sebanyak 16 spesies ikan berhasil dikumpulkan yang terdiri atas satu jenis ikan endemik (M. arfakensis), sembilan jenis ikan asli, dan enam jenis ikan asing. Ikan pelangi arfak dan tiga jenis ikan asli termasuk insektivora, empat jenis ikan asli adalah ikan herbivora, dan dua jenis ikan asli lainnya termasuk ikan karnivora. Tiga spesies ikan asing juga termasuk ikan insektivora, dua jenis ikan asing adalah ikan karnivora, dan satu spesies ikan asing lainnya adalah ikan herbivora. Luas relung komunitas ikan berkisar di antara 0,071-0,857. Tumpang tindih relung makanan ditemukan antara ikan pelangi arfak dengan tiga spesies ikan asli serta tiga spesies ikan asing. Hasil penelitian ini menunjukkan adanya potensi interaksi kompetisi dan pemangsaan antara ikan pelangi arfak dan ikan asli serta dengan ikan asing. Introduksi ikan asing ke dalam sistem Sungai Prafi ditengarai akan mengganggu populasi ikan pelangi arfak.